Pengaruh Model Teams Games Tournament Terhadap Kemampuan Pemahaman Matematik Siswa Kelas XI SMK di Kota Cimahi Pada Materi Fungsi Eksponen - Senja Noviani Dewi; Tommy Tanu Wijaya; Ayu Budianti; Euis Eti Rohaeti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
Education is a conscious and planned effort organized by school institutions to guide and train learners to grow awareness about the existence of life and the ability to solve every problem of life that always arises. It is reminded that teaching and learning activities are held in order to provide students with learning experiences. Selection of learning models used by teachers in delivering taught material can affect learning outcomes. One model of cooperative learning is Teams Games Tournament (TGT) model. The TGT learning model is a group learning model that involves student activity with an exchange of thoughts or ideas constructing knowledge amongst students in groups when getting assigned. This research is a Classroom Action Research (PTK) or Classroom Action Research is a research that is intended to provide information on how appropriate action to improve teachers' ability and student activeness. The results of the implementation of the first cycle of action I have achieved the classical indicator that has reached 62.5% students score above 70 and the results in cycle II reach 92% students score above 70.